LMF: lexical markup framework - Francopoulo, Gil (Computer engineering and IT series, 2013)
The community responsible for developing lexicons for Natural Language Processing (NLP) and Machine Readable Dictionaries (MRDs) started their ISO standardization activities in 2003. These activities resulted in the ISO standard Lexical Markup Framework (LMF).